Hedonism, Desirability and the Incompleteness Objection. (11th March 2019) - Andrić, Vuko
Abstract: Hedonism claims that all and only pleasure is intrinsically good. One worry about Hedonism focuses on the "only" part: Are there not things other than pleasure, such as personal projects and relationships, that are intrinsically good? If so, it can be objected that Hedonism is incomplete. In this paper, I defend Hedonism against this objection by arguing for a distinction between goodness and desirability that understands "desirability" as a deontic concept, in terms of "reason to desire", but goodness as an evaluative concept. Based on this distinction, I attempt to show that Hedonists should accept that things other than pleasure, such as personal projects and relationships, are desirable for their own sakes but deny that these things are intrinsically good [Corrections added on 3 May 2019 after first online publication: The original abstract text is now the first paragraph of the paper's introduction. An updated abstract has been added.]